E-Commerce adoption and its impact on the performance of women-led MSMEs in Metro Manila: An ex-ante study for RCEP - Jill Angeli V. Bacasmas; Jean Clarisse T. Carlos; Jovito Jose P. Katigbak (Philippine Institute for Development Studies (PIDS), 2022)
This ex-ante study analyzes the impacts of e-commerce adoption on the performance of women-led MSMEs in Metro Manila, their awareness and perceptions of government efforts towards internationalization, and their readiness to engage in cross-border e-commerce through the Regional Comprehensive Partnership Agreement (RCEP). Findings validate the observation that the COVID-19 pandemic has accelerated e-commerce adoption and this has substantially enhanced the performance of women-led MSMEs in terms of sales growth, customer base, customer satisfaction, and process enhancement. The data further highlight that there is low level of awareness on both existing government programs for women-led MSMEs, and on RCEP and its chapters on e-commerce and MSMEs. However, certain provisions within the chapters appeal to women -led MSMEs, such as 'information on trade and investment-related laws and regulations for export -oriented MSMEs' and 'acceptance of electronic transaction documents in online cross-border transactions.' Women-led MSMEs in Metro Manila demonstrate strong interest to engage in cross -border trade under RCEP if implemented in 2022. This study also further reveals that a high propensity for cross-border e-commerce - fostered by an enabling policy environment that supports their e-commerce adoption and growth - will potentially heighten the participation in regional trade and the global value chain.
Keywords: 330; MSMEs; RCEP; e-commerce; WoMSMEs; cross-border trade; regional comprehensive economic partnership agreement; women-led businesses